Graphic tool with feeding recommendations for people with obesity undergoing Bariatric and Metabolic Surgery. - López Flores, María de Lourdes (2020)
Objectives: The purpose of this study is to Design and evaluate a graphic tool (GT) with feeding recommendations for people with obesity after bariatric surgery, based on the guidelines proposed by the American Society for Metabolic and Bariatric Surgery (ASMBS), American Association of Clinical Endocrinologists (AACE) y The Obesity Society (TOS) as well as the recommendations of the Mexican College of Surgery for Obesity and Metabolic Diseases (CMCOEM) for the educational use of the nutritionist-Bariatric patient. Methods: A GT named “Graphic tool for post bariatric surgery feeding” was elaborated based on the nutritional guidelines proposed by the ASMBS, AACE and TOS in conjunction with the recommendations of the CMCOEM. In addition to making four graphs representing each of the phases that conform the GT, a self-administered questionnaire was incorporate, it was carried out in three different groups: 27 medical students, 16 pre surgical patients and 8 postsurgical patients. We sought to identify if the perceived message was clear and brief. Results:  More than 70% of the intervened population understood the message of the HG designed, there was no statistical significance among the groups interviewed (p <0.05) without significant difference (p <0.05) between pre and postsurgical patients, in none of the answers. Conclusion: Bariatric nutrition education is essential for the patient to understand the transition of the postsurgical phases, the food groups, the consistency, tolerance and portion of the food. This GT can be useful in the nutritional consultation exclusively for patients who will undergo this type of surgery or are already in the process of recovery.